Urinary equol levels are positively associated with urinary estradiol excretion in women - Tomoko Fujitani (Nature Portfolio, 2021)
Abstract Isoflavones found in soy products are a promising class of nutrients that may have a positive effect on human health. In particular, the phytoestrogen metabolite equol is associated with a reduced risk of developing female hormone-related diseases. However, the effect of equol on estrogen remains unclear. Equol can modify blood and urinary estradiol (E2) levels. The aim of this cross-sectional study was to examine the associations between urinary estrogen levels, equol levels, and equol production status in Japanese women. We analyzed urine samples from 520 women by gas chromatography-mass spectrometry. Urinary E2 and 4-hydroxylated E2 levels were higher in equol producers (EQP) than in non-EQPs (P < 0.0001 and P=0.00112, respectively). After adjusting for age and tobacco use by analysis of covariance, the association remained significant (β = 0.299, P < 0.0001). Analysis of covariance demonstrated that equol levels in urine were also positively associated with urinary E2 (β = 0.597, P < 0.0001). The log equol concentration showed a significant, but moderate, negative association with the serum E2 concentration (β = − 0.0225, P = 0.0462). Our findings suggest that equol may promote urinary E2 excretion and modify blood E2 levels in women.